Penatalaksanaan Holistik Pada Pasien Hipertensi Dan Obesitas Derajat II Dengan Riwayat Stroke Melalui Pendekatan Kedokteran Keluarga - Tania Matalauta Sitepu; Diana Mayasari (CV. Jasa Sukses Abadi, 2020)
Hypertension is one of the non-infectious diseases which becomes an important health problem throughout the world because it keeps increasing. There are 9.4 million deathhs from cardiovascular disease are caused by complications of hypertention. Hypertension itself is a multifactorial disease that arises mainly because of interactions between certain risk factors that can be modified or cannot be modified. Whereas, obesity is caused by an imbalance between the incoming energy and the energy that comes out. The prevalence of obesity throughout the world has tendency to increase in past 30 years.. In addition, Farmingham study stated that 65% of women and 78% of men who suffer from hypertension are directly related to weight gain and obesity. The study was Case Report Study. Primary data is obtained through history taking and physical examination by making home visits, filling out family folders, and filling in patient files. Assessment is carried out based on the initial holistic diagnosis, process, and end of the visit quantitatively and qualitatively. Based on a holistic diagnosis, the patient has a complaint of feeling headache and often followed by a feeling of heaviness behind the neck. The patient also had a history of stroke four years ago. Patient feel worried that the disease is getting worse, has recurrent stroke, and be a burdensome for his family. The patient's expectation is less clinical symptoms , controlled hypertension, no longer obesity, and can do activity and work normally again. Patient was diagnosed with hypertension and obesity in grade II based on the results of history and physical examination. The patient is a 53-year-old man who is obese, often eating foods that contain lots of salt, oily food, and lack of physical activity. Patients are less aware of the disease and the right lifestyle for the illness. After the intervention is done holistically with drugs and education, he obtains a decrease in clinical symptoms and behavioral changes by changing lifestyle and routine taking drugs. Diagnosis and management of this patient has been doing holistically, patients center, family approach based on several theories and current research. In the process of behavior change, patient has reached the trial stage.